Analysis of the elasticity of demand for bread - Marina Lolić Čipčić; Doris Cvitković (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Measures of demand elasticity indicate the direction and intensity of the reaction of the quantity of demand for a good or service due to a change in the determinants of demand. Among them, the price elasticity of demand stands out because it measures the reaction of customers to price changes. Price elasticity is therefore important for management in making pricing decisions because it answers the question of how raising or lowering prices will affect sales revenue and, consequently, the company's financial results. In this paper, the elasticity of demand for selected types of bread from the company Bobis d.o.o. was empirically tested. The listed company is the leader in the production of bread, fresh pastries, confectionery products, and cakes (NKD 2007 10.71) in County of Split-Dalmatia, and, at the same time, one of the top ten entrepreneurs in the same industry at the national level. For the analysis, data on sales volumes and associated prices of bread in forty-four branches within County of Split-Dalmatia in 2022 were used. In the empirical part of the paper, the coefficients of price and income elasticity of demand for selected types of bread were estimated. By comparing the calculated coefficients of price elasticity of demand for selected types of bread before and after the introduction of the pricing campaign, the results point to the conclusion that the demand for bread is price elastic. The range of the calculated coefficients of price elasticity of demand is significantly higher when the campaign is introduced, in other words, the introduction of the pricing campaign reduced the sensitivity of customers to price changes in the short term, i.e. after the end of the pricing campaign sales increase despite the return of prices to the levels that preceded the campaign. Finally, the calculation of the coefficients of income elasticity of demand implies that, for all selected types, bread is considered to be a normal good.